Wistakon Application as Cirebon Smart City Identity Icon - Reza Wahyudi Putra; Tania Lestari Aji; Sri Wulandari; Dedet Erawati (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Cirebon, a city rich in history and culture, seeks to modernize while preserving its unique heritage. As part of its Smart City initiative, there is a need for a unifying symbol that reflects its identity and connects its technological advancements with cultural heritage. Wistakon, a symbol rooted in local tradition, is proposed as the ideal icon for this purpose. The study employs a mixed-method approach, including qualitative interviews with local stakeholders (government officials, cultural experts, and residents) and quantitative surveys to gauge public perception and acceptance of Wistakon as a city icon. Additionally, an analysis of successful case studies from other smart cities using cultural icons will be conducted to draw best practices.This research aims to conduct a performance study of the Wistakon Application service as an identity icon for Cirebon smart city. In this research, researchers examine the weaknesses and obstacles that arise when this application is used by domestic tourists. Apart from that, researchers also studied the benefits of the Wistakon application. The literature study used is the Integrated Guest-Operator Framework (IGOF) Theory as a framework for understanding the relationship between tour operators and tourist guests in the context of the tourism industry. This theory emphasizes the importance of integration and balance between the needs and expectations of tourist guests with the strategies and operations carried out by tour operators. Based on the results of the study, researchers concluded that the Wistakon application still needs development, socialization and promotion.